2006
DOI: 10.1007/s10582-006-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of needle electrodes in pulsed corona discharge in water

Abstract: Erosion of needle electrodes in the pulsed corona discharge in water with a pulse energy of ∼ 2÷; 3 J was investigated in dependence on the electrode material (platinum, tungsten and stainless-steel) and the solution conductivity (100 and 500 µS/cm). Erosion of electrodes remarkable increased with the higher solution conductivity for all three tested metals. The highest erosion rates were determined for tungsten while platinum was the least eroded material. In addition to the dominant melting effect, release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 9 publications
3
53
0
Order By: Relevance
“…Needle electrodes made of tungsten carbide and tungsten copper alloy were characterized by erosion rates three times higher than materials with the lowest erosion rates. The gravimetric erosion rate measured for stainless steel (0.55 lg/s) is in good agreement with the result published by Lukes et al [10]. The erosion rates for thoriated tungsten and the diamond-coated tungsten electrode (1.43 and 1.28 lg/s) were within the range of the value measured for pure tungsten by Lukes et al [10].…”
Section: H 2 O 2 Formation Studies With Different Needle Electrode Masupporting
confidence: 91%
See 4 more Smart Citations
“…Needle electrodes made of tungsten carbide and tungsten copper alloy were characterized by erosion rates three times higher than materials with the lowest erosion rates. The gravimetric erosion rate measured for stainless steel (0.55 lg/s) is in good agreement with the result published by Lukes et al [10]. The erosion rates for thoriated tungsten and the diamond-coated tungsten electrode (1.43 and 1.28 lg/s) were within the range of the value measured for pure tungsten by Lukes et al [10].…”
Section: H 2 O 2 Formation Studies With Different Needle Electrode Masupporting
confidence: 91%
“…Plasma pressure and shockwaves cause bursting of these bubbles and the release of electrode material into the surrounding media [14,16]. To our knowledge, very few studies on electrode erosion in an aqueous high voltage discharge reactor have been reported in the literature [7][8][9][10]. Kirkpatrick and Locke [8] found using platinum and nickel chromium needle electrodes that approximately 0.55 lg/s of both electrode materials were released into the solution during 1 h of operation of the reference reactor.…”
Section: H 2 O 2 Formation Studies With Different Needle Electrode Mamentioning
confidence: 99%
See 3 more Smart Citations